SOCIAL CONFLICTS ANALYSIS IN LILY YULIANTI’S SELECTED SHORT STORIES - Astarita, Dewanty; Halim, Abdul (ELITERATE : Journal of English Linguistics and Literature Studies, 2022)
This study aims to determine the types of social conflicts that occur, the influential factors of social conflicts, and the effects that occur on each main character in the selected short story by Lily Yulianti. This study uses a qualitative descriptive method and strukturalism approach based on the social conflict theory of Lewis A. Coser. The data in this study were taken from 3 out of 17 short stories summarized in one book, with each title being 'Kitchen', 'Family Room', and 'Nua, Diani, and Male Leaps'. The conclusions of this study are (1) there are 3 types of social conflicts that occur in the story; Conflict of Interest, Conflict of Social Status, and Conflict of Role, (2) as for the factors that influence the occurrence of the conflict; Bureaucracy, Family Disorganization, Problems of the Young Generation in Modern Society, and Environmental Problems, and (3) the effects that occur on each of the main characters in the story; family disharmony, personality changes, depression, resentment, social and psychological trauma, and gender discrimination against men.